Acellular Gelatinous Material of Human Umbilical Cord Enhances Wound Healing: A Candidate Remedy for Deficient Wound Healing - Bakhtyar, Nazihah; Jeschke, Marc G.; Mainville, Laurence; Herer, Elaine; Amini-Nik, Saeid (Frontiers in Physiology, 2017)
Impaired wound healing is a severe clinical challenge and research into finding effective wound healing strategies is underway as there is no ideal treatment. Gelatinous material from the umbilical cord called Wharton’s jelly is a valuable source of mesenchymal stem cells which have been shown to aid wound healing. While the cellular component of Wharton’s jelly has been the subject of extensive research during the last few years, little is known about the de-cellularized jelly material of the umbilical cord. This is important as they are native niche of stem cells. We have isolated Wharton’s jelly from umbilical cords and then fractionated acellular gelatinous Wharton’s jelly (AGWJ). Here, we show for the first time that AGWJ enhances wound healing in vitro as well as in vivo for wounds in a murine model. In vivo staining of the wounds revealed a smaller wound length in the AGWJ treated wounds in comparison to control treatment by enhancing cell migration and differentiation. AGWJ significantly enhanced fibroblast cell migration in vitro. Aside from cell migration, AGWJ changed the cell morphology of fibroblasts to a more elongated phenotype, characteristic of myofibroblasts, confirmed by upregulation of alpha smooth muscle actin using immunoblotting. AGWJ treatment of wounds led to accelerated differentiation of cells into myofibroblasts, shortening the proliferation phase of wound healing. This data provides support for a novel wound healing remedy using AGWJ. AGWJ being native biological, cost effective and abundantly available globally, makes it a highly promising treatment option for wound dressing and skin regeneration.